Comparison of a molecular and an immobilized gadolinium(III)-tris[(1R,4S)-3-heptafluorobutanoyl-camphor] as catalyst in the asymmetric Danishefsky-hetero-Diels-Alder-reaction - Stockinger, Skrollan Carina; Trapp, Oliver (Chirality, 2014)
On-column reaction gas chromatography combines the power of separation and rapid analysis of reactants and reaction products with screening of reactions in a single step. Not only conversions but the reaction rates at various temperatures can be obtained from single measurements, making this approach superior to the time-consuming measurements typically performed in reaction progress analysis. However, this approach has only been used in the investigation of interconversion processes, rearrangement reactions, and only a few examples of higher-order reactions are known. Here we present the screening of immobilized gadolinium(III)-tris[(1R,4S)-3-heptafluorobutanoyl-camphor] in the Danishefsky-hetero-Diels-Alder-reaction by enantioselective on-column reaction gas chromatography utilizing cryogenic focusing to achieve catalytic conversions in this higher-order reaction and subsequent separation of the enantiomeric product mixture to determine the enantiomeric ratio. The results obtained by this approach could be transferred to the conventional batch reaction at a larger scale, demonstrating that on-column reaction chromatography provides reliable results in the screening of enantioselective reactions. Chirality 26:243-248, 2014. © 2014 Wiley Periodicals, Inc.
Gesehen am 31.07.2020